The Effect of Project-Based Strategies and Learning Motivation on Student Engagement in the Learning Process at AMIK Bukittinggi - Dennis Haruna; Darul Ilmi (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Student engagement is a key indicator in determining the quality of the learning process at higher education institutions. However, student engagement at AMIK Bukittinggi remains suboptimal, as evidenced by low participation in discussions, a lack of confidence in expressing opinions, and limited involvement in learning activities. This study aims to analyze the influence of Project-Based Learning Strategies and Learning Motivation on Student Engagement in the learning process at AMIK Bukittinggi. The study employed a quantitative approach with an associative research design. The study population consisted of 132 active students in the Information Management Study Program at AMIK Bukittinggi for the 2025/2026 academic year, with a sample of 99 students determined using the Slovin formula and the Proportionate Stratified Random Sampling technique. Data were collected via a questionnaire and analyzed using multiple linear regression. The results indicate that Project-Based Strategies have a positive and significant effect on Student Engagement (t = 2.982; sig. = 0.033). Learning Motivation also has a positive and significant effect on Student Engagement (t = 3.713; sig. = 0.000) and is the variable with the more dominant influence. Simultaneously, Project-Based Strategies and Learning Motivation have a significant effect on Student Engagement (F = 23.400; sig. = 0.000) with a coefficient of determination (R²) of 0.328. This study concludes that student engagement can be enhanced by optimizing the implementation of Project-Based Strategies and strengthening Learning Motivation in the learning process.